The IFN-induced protein IFI27 binds MDA5 and counteracts its activation after SARS-CoV-2 infection - Rivero, Vanessa; Carrión-Cruz, Julia; López-García, Darío; DeDiego, Marta L. (Frontiers in Cellular and Infection Microbiology, 2024)
Innate immune responses are induced after viral infections, being these responses essential to establish an antiviral response in the host. The RIG-I-like receptors (RLRs), RIG-I and MDA5 are pivotal for virus detection by recognizing viral RNAs in the cytoplasm of infected cells, initiating these responses. However, since excessive responses can have a negative effect on the host, regulatory feedback mechanisms are needed. In this work, we describe that IFN alpha-inducible protein 27 (IFI27) co-immunoprecipitates with melanoma differentiation-associated protein 5 (MDA5), being this interaction likely mediated by RNAs. In addition, by using IFI27 overexpression, knock-out, and knock-down cells, we show that IFI27 inhibits MDA5 oligomerization and activation, counteracting the innate immune responses induced after SARS-CoV-2 infections or after polyinosinic-polycytidylic acid (poly(I:C)) transfection. Furthermore, our data indicate that IFI27 competes with MDA5 for poly(I:C) binding, providing a likely explanation for the effect of IFI27 in inhibiting MDA5 activation. This new function of IFI27 could be used to design target-driven compounds to treat diseases associated with an exacerbated induction of innate immune responses, such as those induced by SARS-CoV-2.